2013
DOI: 10.1093/cvr/cvt065
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin (1–7) counteracts the negative effect of angiotensin II on insulin signalling in HUVECs

Abstract: In endothelial cells angiotensin (1-7) counteracts the negative effects of angiotensin II on insulin signalling and NO production. The balance between angiotensin II and angiotensin (1-7) could represent a key mechanism in the pathophysiological processes leading to endothelial dysfunction and insulin-resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…However, in C57Bl/6 mice, MAS knockout does not alter blood pressure ). Short-term Ang(1-7) infusion in normotensive rats enhanced endothelial function (Faria-Silva et al, 2005), which may be also be conserved in other species (Langeveld et al, 2008;Durand et al, 2010;Beyer et al, 2013;Jarajapu et al, 2013;Tassone et al, 2013).…”
Section: G Pathophysiological Evidence Of Mas Receptor Interaction Wmentioning
confidence: 86%
“…However, in C57Bl/6 mice, MAS knockout does not alter blood pressure ). Short-term Ang(1-7) infusion in normotensive rats enhanced endothelial function (Faria-Silva et al, 2005), which may be also be conserved in other species (Langeveld et al, 2008;Durand et al, 2010;Beyer et al, 2013;Jarajapu et al, 2013;Tassone et al, 2013).…”
Section: G Pathophysiological Evidence Of Mas Receptor Interaction Wmentioning
confidence: 86%
“…In the FVB/N mouse background, the endothelial dysfunction is associated with an increase in blood pressure , whereas in C57Bl/6 mice, no alteration of blood pressure was observed . The endothelial dysfunction associated with Mas deficiency in two genetic backgrounds is in Mas-Related Genes keeping with the improvement of endothelial function produced by short-term Ang-(1-7) infusion in normotensive rats (Faria-Silva et al, 2005) and with the improvement of Mas-mediated vascular function in many species and conditions (Langeveld et al, 2008;Durand et al, 2010;Stegbauer et al, 2011;Beyer et al, 2013;Jarajapu et al, 2013;Tassone et al, 2013).…”
Section: Mas-related G Protein-coupled Receptors and Mas In Cardiomentioning
confidence: 66%
“…It was found that Ang-(1-7) not only counteracted the AngII-mediated inhibition of insulin-stimulated Akt phosphorylation, but also improved the phosphorylation of other insulin-related intracellular proteins, such as AS160 and GSK-3β [86]. In a recent report, this counteraction of the inhibitory effects of AngII on insulin-induced Akt activation was confirmed using both human umbilical vein endothelial cells [140] and isolated rat soleus muscle [141]. Importantly, in skeletal muscle, Ang-(1-7) was shown to ameliorate the inhibitory effect of AngII on glucose transport activity [141].…”
Section: Ang-(1-7) Counteracts the Negative Effects Of Angii On The Amentioning
confidence: 78%
“…Importantly, in skeletal muscle, Ang-(1-7) was shown to ameliorate the inhibitory effect of AngII on glucose transport activity [141]. Although the negative effects of AngII on insulin signalling are mediated by the AT 1 R, the beneficial and counteracting effect of Ang-(1-7) on the actions of AngII at this level appear to be mediated by its specific receptor Mas [92,140,141] (Figure 3A).…”
Section: Ang-(1-7) Counteracts the Negative Effects Of Angii On The Amentioning
confidence: 97%